A necrotic lung ball caused by co-infection with Candida and Streptococcus pneumoniae - Yokoyama, Toshinobu (Dove Medical Press, 2011)
INTRODUCTION: A necrotic lung ball is a rare radiological feature that is sometimes seen in cases of pulmonary aspergillosis. This paper reports a rare occurrence of a necrotic lung ball in a young male caused by Candida and Streptococcus pneumoniae. CASE REPORT: A 28-year-old male with pulmonary candidiasis was found to have a lung ball on computed tomography (CT) of the chest. The patient was treated with β-lactams and itraconazole and then fluconazole, which improved his condition (as found on a following chest CT scan) and serum β-D-glucan level. The necrotic lung ball was suspected to have been caused by coinfection with Candida and S. pneumoniae. CONCLUSION: A necrotic lung ball can result from infection by Candida and/or S. pneumoniae, indicating that physicians should be aware that patients may still have a fungal infection of the lungs that could result in a lung ball, even when they do not have either Aspergillus antibodies or antigens.